Reconfigurable Logic Embedded Architecture of Support Vector Machine Linear Kernel - Jeevan Sirkunan; N. Shaikh-Husin; Trias Andromeda; M. N. Marsono (IAES Indonesia Section, 2017)
Support Vector Machine (SVM) is a linear binary classifier that requires a kernel function to handle non-linear problems. Most previous SVM implementations for embedded systems in literature were built targeting a certain application; where analyses were done through comparison with software im- plementations only. The impact of different application datasets towards SVM hardware performance were not analyzed. In this work, we propose a parameterizable linear kernel architecture that is fully pipelined. It is prototyped and analyzed on Altera Cyclone IV platform and results are verified with equivalent software model. Further analysis is done on determining the effect of the number of features and support vectors on the performance of the hardware architecture. From our proposed linear kernel implementation, the number of features determine the maximum operating frequency and amount of logic resource utilization, whereas the number of support vectors determines the amount of on-chip memory usage and also the throughput of the system.